A revisit of pressure drop-flow rate correlations for packed beds of spheres - ERKEN, ESRA; AKGİRAY, ÖMER (ELSEVIER SCIENCE BV, 2015)
A large number of correlations can be found in the literature for the calculation of pressure drop caused by fluid flow through packed beds. New correlations continue to be proposed and there appears to be no general agreement regarding which correlation is the most accurate. In this work, experiments have been carried out with water using glass spheres of nine different sizes, varying from 1.18 mm to 9.99 mm. For each size, experiments were repeated with at least two different porosities. A total of 38 correlations from the literature have been evaluated and a uniform notation was established to facilitate the comparison of the correlations. While the Ergun equation remains the most widely-used correlation, the data collected in this work shows that it should not be used above Re-m approximate to 500. A simple new equation (f(v) = 160 + 2.81Re(m)(0.904)) is proposed to represent the data collected in this work. The new equation yields the smallest mean error among all the correlations considered here. While a substantial amount of the data collected in this work involved D/d(p) ratios less than 10, the correlations that fit the current data best do not have any wall effect correction terms. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Head loss; Packed bed; Porous media; Pressure drop; POROUS-MEDIA; REYNOLDS-NUMBERS; FILTER EXPANSION; EQUATION; WALL; PREDICTION; EXTENSION; PARTICLES; PACKINGS; COLUMNS